Quality of Chatbot Responses to the Most Popular Questions Regarding Erectile Dysfunction - İrfan Şafak Barlas; Lütfi Tunç (Urology Research and Practice)
Objective: Erectile dysfunction (ED) is a common cause of male sexual dysfunction. We aimed to evaluate the quality of ChatGPT and Gemini’s responses to the most frequently asked questions about ED.